Geneza i rola drzew w mitologii japońskiej w świetle Kojiki i Nihongi - Wesołowski, Dawid (Motywy fauny i flory w literaturze i kulturze, 2018)
Animistic cults and religions are characterized by belief, that every part of the world, both alive and inanimate, contain soul or spirit. One of those is Japanese indigenous religion — shintō. The world of Japanese mythology revolves around anthropomorphic deities — kami and countless spirits that manifests in fauna, flora and in various phenomena of nature. Description of creation of the world and all its elements was written down in chronicles Kojiki and Nihongi. Cosmogony in Japanese mythology equals teogony and thanks to that it is possible to analyze origin of trees, as well as genealogy of deities responsible for that part of the flora. By studying texts of chronicles in Polish and English translations along with Japanese original I would like to show mythical beginnings of specific trees in Japan — first ancestor and origin of specific species — and role they played in history of a mythical heroes. Among others, paper presents theory of origin of sakaki and also a potential identification of the uncanny tree that grew near Uki river.